Investigation of AA5083 T-lap joint fabricated by friction stir welding - Nhan, Phan Thanh; Khang, Tran Minh; Tra, Tran Hung (Vietnam Journal of Science and Technology, 2019)
Transportation industries are faced to big maters that the scientists focus on, such as energy saving and ecologically sustainable products. Therefore, many innovative solutions are delivered that will support environmental preservation but meet industries’ requirements for greater productivity and minimized operational costs. Aluminium alloys have successfully contributed to meeting the rising demand for lightweight structures. Recently, notable developments in aluminium welding techniques have resolved many welding related problems, although some problems need to be addressed. In this paper, 5083 aluminium alloy T-lap-joints were successfully fabricated by friction stir welding with various welding regimes. The defects morphology in the T-joints was experimentally observed and analyzed by a high magnification microscope. The roles of the grain microstructure and the effects of defects morphology in the mechanical behavior of the T-joint was investigated. In addition, the fracture locations and the fracture surface of the failure specimens were observed and discussed as well. Results indicate that the fracture of T-joints along the stringer is attributed to the bonding line defects, kissing bond defects and the tunnel defects. The result also shows, in the T-joints of 5083 aluminum alloy, the welding parameters influence significantly on the features and sizes of the defects.